Argumentative essay as an example of text-argument (in the English language) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
Logic-structural peculiaritys of reasoning texts composition being analysed and delineated their main text-forming parameters. Text typology problem on the level of speech composition being investigated, taking into account lingvo-stylistical factors.
Keywords: reasoning texts; composition; logic-structural peculiarities; typology; essay